Pengaruh Pembelajaran dengan Menggunakan Media Gambar Terhadap Pemahaman Siswa pada Tema Peduli Terhadap Makhluk Hidup Siswa Kelas IV Di Sekolah Dasar - Faizal Chan; Sri Wahyuni (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2016)
The purpose of this study was to determine the effect of using media images on learning comprehension in class IV students. The hypothesis of this study is the use of picture media influences the learning comprehension of fourth grade students of SDN No.186 / 1 Sridadi. This type of research is experimental research with a research population of fourth grade students SDN No.186/1993 in the academic year 2014/2015 as many as I Class. The sample consisted of 2 classes namely class IV, which amounted to 30 students divided into II classes namely class IV.I (experimental class) and class IV.II (control class). Based on the results of the research obtained, the average class IV.I = 7.37 higher than class IV.II = 6.5. After analyzed using Test t obtained t table of 1.701 and tcount 2.41. Because tcount> t table (2.41> 1.701) then the price of 2.41 is at Ha revenue. then Ha is accepted and Ho is rejected. So there are differences in students' understanding of learning in class IV.I and class IV.II. It can be concluded that the use of gamelan media can influence the learning comprehension of fourth grade students at SDN No.186 / 1 Sridadi.